Resisting linguistic imperialism in English teaching - Canagarajah, A. Suresh (Oxford applied linguistics., 1999)
"This book describes the creative strategies employed by teachers and students in periphery communities to use the English language in a manner that suits their needs and aspirations while subtly resisting the linguistic imperialism that many scholars have identified as the consequence of the global ELT enterprise. After developing trends and ideas from these oppositional strategies, the book goes on to outline elements of critical pedagogy suitable for English Language Teaching in formerly colonized communities."--BOOK JACKET.